School and work : does the Eastern Caribbean education system adequately prepare youth for the global economy? (World Bank WashingtonUS, 2007)
Reviews current education and skills training options in the OECS. Examines how the economic transformation of the Eastern Caribbean affects the demand for education and skills. Considers the Caribbean Single Market and Economy and the resulting free movement of labour, and the implications this has for common standards and certification. Makes the case for the reason why the OECS education and training systems need to be more responsive to changing labour market demands in the region. Discusses how this could be achieved, taking into consideration the latest education and training policies in the region.
Keywords: EDUCATION